Risk Analysis on the Growth Rate of Covid-19 Cases in Indonesia Using Statistical Distribution Model - Utari, Dina Tri; Hendradewa, Andrie Pasca (Universitas Islam Indonesia, 2021)
Coronavirus or Covid-19 outbreak has been declared as a pandemic and many countries were not ready to deal with such an eventuality. The highly rapid rate of transmission is one reason for the need to take mitigation measures, since healthcare system has limited capacity. Indonesia is one of the countries that has lost medical resources to the pandemic. In order to provide more comprehensive information about the characteristics of Covid-19 in Indonesia, risk analysis of the occurrence of new cases was needed. This study proposes a related overview about risk occurrence of new Covid-19 cases per daily basis by performing distribution fitting technique to form a statistical distribution model. Among the available alternative models, Geometric distribution is the most suitable to describe the growth of new cases in Indonesia. Received February 12, 2021Revised March 25, 2021Accepted April 15, 2021